2014
DOI: 10.5713/ajas.2013.13493
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Metabolism in Lactating Goats Fed with Diets Containing Different Protein Sources

Abstract: This study aimed to evaluate urea excretion, nitrogen balance and microbial protein synthesis in lactating goats fed with diets containing different protein sources in the concentrate (soybean meal, cottonseed meal, aerial part of cassava hay and leucaena hay). Four Alpine goats whose mean body weight was 42.6±6.1 kg at the beginning of the experiment, a mean lactation period of 94.0±9.0 days and a production of 1.7±0.4 kg of milk were distributed in a 4×4 Latin square with four periods of 15 days. Diets were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…In contrast, in the extensive mode of goat keeping the increase in the proportion of crude protein in the supplementary portion of the diet has no effect the milk urea concentration (Cabiddu et al, 1999;Bava et al, 2001;Todaro et al, 2005;Bonanno et al, 2008). In addition, Santos et al (2014) aimed to assess the degree of urea excretion and the synthesis of microbial proteins in Alpine goats fed a diet containing different sources of protein in the concentrate (soy, a meal composed of cotton seeds, cassava hay and alfalfa hay). These authors found the highest concentration of urea in the blood and milk in goats fed with soybeans and cotton seeds, which explains the better breakdown of protein in the rumen due to insufficient matching in carbon and nitrogen structure used by microorganisms during urea synthesis.…”
Section: Reduced Dietary Protein Intake May Results In Changesmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, in the extensive mode of goat keeping the increase in the proportion of crude protein in the supplementary portion of the diet has no effect the milk urea concentration (Cabiddu et al, 1999;Bava et al, 2001;Todaro et al, 2005;Bonanno et al, 2008). In addition, Santos et al (2014) aimed to assess the degree of urea excretion and the synthesis of microbial proteins in Alpine goats fed a diet containing different sources of protein in the concentrate (soy, a meal composed of cotton seeds, cassava hay and alfalfa hay). These authors found the highest concentration of urea in the blood and milk in goats fed with soybeans and cotton seeds, which explains the better breakdown of protein in the rumen due to insufficient matching in carbon and nitrogen structure used by microorganisms during urea synthesis.…”
Section: Reduced Dietary Protein Intake May Results In Changesmentioning
confidence: 99%
“…, reproductive traits of goats (Godden et al, 2001a;Marenjak et al, 2004;Mellado et al, 2004;Butler, 2005;Biswajit et al et al, 2011), milk processing properties (Pretto et al, 2013;Bland et al, 2015) and environmental pollution (Santos et al, 2014).…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the levels of serum uric acid found, diets with a higher crude protein level can induce a small increase in these levels (42). Varying feed composition, mainly by considering different batches of silage supplied during the experiment, could result in a small increase in uric acid levels in the second, third, and fourth weeks.…”
Section: Discussionmentioning
confidence: 99%
“…In such context, among the alternatives for yielding of industrial byproducts animal feeding shows great potential [ 4 6 ], since the increase in prices of vegetal supplementation used for animal feeding has aroused great interest by the yielding of nonconventional food. However, so that the correct use of such byproducts be performed, it is necessary to verify nutrition adequacy of such ingredients [ 2 , 7 ]. This is important, for the correct formulation of diets for animals goes beyond fulfilling nutrition needs, including the quality of final product and fulfilling the expectations of consumers.…”
Section: Introductionmentioning
confidence: 99%